The Lysine Deacetylase RpdA Is Essential for Virulence in Aspergillus fumigatus - Bauer, Ingo; Misslinger, Matthias; Shadkchan, Yana; Dietl, Anna-Maria; Petzer, Verena; Orasch, Thomas; Abt, Beate; Graessle, Stefan; Osherov, Nir; Haas, Hubertus (Frontiers in Microbiology, 2019)
Current suboptimal treatment options of invasive fungal infections and emerging resistance of the corresponding pathogens urge the need for alternative therapy strategies and require the identification of novel antifungal targets. Aspergillus fumigatus, is the most common airborne opportunistic mold pathogen causing invasive and often fatal disease. Establishing a novel in vivo conditional gene expression system, we demonstrate that downregulation of the class 1 lysine deacetylase (KDAC) RpdA leads to avirulence of A. fumigatus in a murine model for pulmonary aspergillosis. The xylP promoter used has previously been shown to allow xylose-induced gene expression in different molds. Here, we demonstrate for the first time that this promoter also allows in vivo tuning of A. fumigatus gene activity by supplying xylose in the drinking water of mice. In the absence of xylose, an A. fumigatus strain expressing rpdA under control of the xylP promoter, rpdAxylP, was avirulent and lung histology showed significantly less fungal growth. With xylose, however, rpdAxylP displayed full virulence demonstrating that xylose was taken up by the mouse, transported to the site of fungal infection and caused rpdA induction in vivo. These results demonstrate that (i) RpdA is a promising target for novel antifungal therapies and (ii) the xylP expression system is a powerful new tool for in vivo gene silencing in A. fumigatus.